Auf der Suche nach dem Anderen in der Wiederkehr des Gleichen. Heiner Müllers Bildbeschreibung zwischen post-historischen Endzeitfantasien und Hoffnung auf Geschichte am Ende des Kalten Krieges - Zenetti, Thomas (Studia Germanica Posnaniensia, 2013)
Bildbeschreibung, written in 1984, is undoubtedly the most hermetic text in the work of the East-German dramatist Heiner Müller. In this prose text, referred to by its author as ‘a play’, an ungraspable “I” vainly attempts to piece together an image to construct a coherent whole. When one compares this with Müller’s other works, Bildbeschreibung makes disconcerting reading because of its apparent lack of any political dimension. A thorough analysis however reveals that the traumas of Germany’s twentieth century history underpin the narrative. Moreover, the desperate attempts by the “I” to build itself into a proper “self” through the (re)-construction of the undecipherable image, hark back to the difficulties one has to conceptualize History after the end of what Jean-François Lyotard calls ‘the grand narratives’. Bildbeschreibung stages these difficulties in terms of history as drama. The “landscape between steppe and savannah” under “a Prussian blue sky” turns out to be the GDR in the 1980s, a country tossed and torn between the anguish of the ending of the historical process as described by the theories of post-history and the hope of a new dynamism made possible by the end of the Cold War.